Model Kebijakan Mutu Pendidikan Berbasis Meta-Leadership untuk Daya Saing Global Indonesia - Windo, Nofel; Handoyo, Eko; Rokhman, Fathur (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to reconstruct education quality policy in Indonesia by employing a meta-leadership approach as a strategic response to increasing global competitiveness amid technological disruption. The primary challenge lies in persistent policy fragmentation, particularly within cross-ministerial governance structures that operate under differing mandates and interests. This condition hinders the integration of digital transformation, the strengthening of character education, and the development of future-oriented skills. This study adopts a systematic literature review method using the PRISMA protocol to synthesize relevant literature on education policy, leadership, and digital transformation. The findings reveal that conventional leadership approaches are insufficient to address the complexity of policy management involving multiple actors and sectors. In this context, meta-leadership functions as an integrative mechanism by enhancing cross-ministerial coordination to align policies, reduce fragmentation, and improve implementation effectiveness. Furthermore, this study proposes a conceptual model of education quality policy that is integrative, adaptive, and collaborative.